The global seroprevalence of anti-Toxoplasma gondii antibodies in women who had spontaneous abortion: A systematic review and meta-analysis. - Tooran Nayeri; Shahabeddin Sarvi; Mahmood Moosazadeh; Afsaneh Amouei; Zahra Hosseininejad; Ahmad Daryani (Public Library of Science (PLoS), 2020)
BACKGROUND:Toxoplasma gondii (T. gondii) is an intracellular pathogen that can lead to abortion in pregnant women infected with this parasite. Therefore, the present study aimed to estimate the global seroprevalence of anti-T. gondii antibodies in women who had spontaneous abortion based on the results of published articles and evaluate the relationship between seroprevalence of anti-T. gondii antibodies and abortion via a systematical review and meta-analysis. METHODS:Different databases were searched in order to gain access to all studies on the seroprevalence of anti- T. gondii antibodies in women who had spontaneous abortion and association between seroprevalence of anti-T. gondii antibodies and abortion published up to April 25th, 2019. Odds ratio (OR) and the pooled rate seroprevalence of T. gondii with a 95% confidence interval (CI) were calculated using the random effects model. RESULTS:In total, 8 cross-sectional studies conducted on 1275 women who had abortion in present pregnancy, 40 cross-sectional studies performed on 9122 women who had a history of abortion, and 60 articles (involving 35 cross-sectional studies including 4436 women who had spontaneous abortion as case and 10398 as control and 25 case-control studies entailing 4656 cases and 3178 controls) were included for the final analyses. The random-effects estimates of the prevalence of anti-T. gondii IgG antibody in women who had abortion in present pregnancy and women who had a history of abortion were 33% (95% CI: 17%-49%) and 43% (95% CI: 27%-60%), respectively. In addition, the pooled OR for anti-T. gondii IgG antibody in cross-sectional and case-control studies among women who had spontaneous abortion were 1.65 (95% CI: 1.31-2.09) and 2.26 (95% CI: 1.56-3.28), respectively. Also, statistical analysis showed that the pooled OR of the risk of anti-T. gondii IgM antibody 1.39 (95% CI: 0.61-3.15) in cross-sectional and 4.33 (95% CI: 2.42-7.76) in case-control studies. CONCLUSION:Based on the results of the current study, T. gondii infection could be considered a potential risk factor for abortion. It is recommended to carry out further and more comprehensive investigations to determine the effect of T. gondii infection on abortion to prevent and control toxoplasmosis among pregnant women around the world.